(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the microscopic characteristics of testicular tissue following the administration of the herbal formula Hoa dam sinh tinh decoction in an experimental model. Subjects and methods: Male white rats with induced testicular dysfunction were administered the study drug. Post-treatment testicular samples were microscopically evaluated for the following parameters: testicular weight, seminiferous tubule diameter, germinal epithelium thickness, Johnsen score, germ cell count, and testicular interstitium. Results: The seminiferous tubule diameter, germinal epithelium height, and Johnsen score in both treatment groups significantly increased compared to those of group 1 and group 2 (p < 0.05). The number of germinal epithelial cells in the 45 g/kg/day dose group increased compared to the induced dysfunction group and the distilled water group, particularly for spermatids (p < 0.05) Conclusion: The herbal formula Hoa dam sinh tinh decoction increases seminiferous tubule diameter, germinal epithelium height, and germ cell count, and improves the Johnsen score compared to the induced dysfunction group when administered at a dose of 45 g/kg/day in an experimental model.